Pathogenetic Therapy for Inflammatory Diseases of the Throat in Children - Ye.I. Yulish; O.Ye. Chernyshova; B.I. Krivuschev; Ye.V. Glinskaya; A.A. Levchenko (Zaslavsky O.Yu., 2013)
This paper presents the data on methods of relief of the inflammatory process in pharyngitis and tonsillitis in children. The mechanism of action of local therapeutic agents is considered.